2021
DOI: 10.1073/pnas.2102889118
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free reconstitution reveals the molecular mechanisms for the initiation of secondary siRNA biogenesis in plants

Abstract: Secondary small interfering RNA (siRNA) production, triggered by primary small RNA targeting, is critical for proper development and antiviral defense in many organisms. RNA-dependent RNA polymerase (RDR) is a key factor in this pathway. However, how RDR specifically converts the targets of primary small RNAs into double-stranded RNA (dsRNA) intermediates remains unclear. Here, we develop an in vitro system that allows for dissection of the molecular mechanisms underlying the production of trans-acting siRNAs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 64 publications
1
21
0
1
Order By: Relevance
“…Although the evidence against RISC-generated cleavage fragments as triggers of siRNA production via RDR6 from this and previous work ( 11 , 42 , 78 , 84 , 85 ) is now compelling, aberrant RNA clearly can play a role in RDR-mediated siRNA amplification given the many reports of ectopic siRNA production in mutants in mRNA decay ( 33–41 ). How may these seemingly opposing pieces of evidence be reconciled?…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although the evidence against RISC-generated cleavage fragments as triggers of siRNA production via RDR6 from this and previous work ( 11 , 42 , 78 , 84 , 85 ) is now compelling, aberrant RNA clearly can play a role in RDR-mediated siRNA amplification given the many reports of ectopic siRNA production in mutants in mRNA decay ( 33–41 ). How may these seemingly opposing pieces of evidence be reconciled?…”
Section: Discussionmentioning
confidence: 78%
“…Likewise, AGO7-miR390 is capable of triggering TAS3 secondary siRNAs from uncleavable miR390 sites in TAS3 precursor RNAs ( 78 ). In addition, recent recapitulation of AGO1-miR173- and AGO7-miR390-triggered tasiRNA generation in cell-free systems showed that RDR6 and AGO physically associate in RISC:target associations leading to tasiRNA production, thus verifying a central element of the RISC trigger model ( 79 , 80 ). In the following, we offer an interpretation of the results described here within the framework of the RISC-trigger model.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, 22‐nt siRNAs and/or siRNAs exhibiting an asymmetric bulge at their duplex were supposed to change AGO1 conformation (Manavella et al, 2012). This new conformation could not only impair the RNase activity of AGO1, but could also recruit RDR6 to the 3ʹ of the target transcript, conceivably with the aid of mediators such as SDE3 and SGS3 (Garcia et al, 2012; Sakurai et al, 2021). Although 22‐nt miRNAs are demonstrated to cleave the target RNAs, our study shows 22‐nt siRNAs have evidently a different mode of action than 22‐nt miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting primary dsRNAs are processed into siRNAs, initiating target RNA silencing (Parent et al, 2015; Wassenegger and Krczal, 2006). In addition, it has been demonstrated that RDR6 is recruited to transcripts that are targeted by (primary) siRNAs for the generation of dsRNA and secondary siRNAs, which map upstream and downstream of the primary siRNA site, a process termed transitivity (Bleys et al, 2006a,b; Chen et al, 2010; Cuperus et al, 2010; Koscianska et al, 2005; Manavella et al, 2012; Mlotshwa et al, 2008; Moissiard et al, 2007; Montgomery et al, 2008a,b; Sakurai et al, 2021; Vaistij and Jones, 2009; Vaistij et al, 2002; Vermeersch et al, 2010, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation